2017
DOI: 10.1088/1361-6463/aa9d79
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the magnetism of cobalt-, manganese-, and nickel-ferrite nanoparticles

Abstract: The microstructure, composition and magnetism of CoFe 2 O 4 , MnFe 2 O 4 and NiFe 2 O 4 nanoparticles of comparable sizes (∼20 nm) and interparticle spacings (∼20 nm) have been characterized from 10 to 400 K. The cation distributions of the tetrahedral and octahedral sites of the particles, that have cubic spinel structures, have a high degree of inversion, ∼0.98 for CoFe 2 O 4 , ∼0.80 for MnFe 2 O 4 and NiFe 2 O 4 nanoparticles. The blocking temperatures were ∼300 K for the MnFe 2 O 4 and NiFe 2 O 4 nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 64 publications
1
23
1
Order By: Relevance
“…Therefore, H d size distributions are greater than the core diameter observed by TEM. Demirci et al [ 67 ] found the particle agglomerations in size range ~60–300 nm for MnFe 2 O 4 nanoparticles. For biomedical applications, hydrodynamic diameter and the PDI are critical parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, H d size distributions are greater than the core diameter observed by TEM. Demirci et al [ 67 ] found the particle agglomerations in size range ~60–300 nm for MnFe 2 O 4 nanoparticles. For biomedical applications, hydrodynamic diameter and the PDI are critical parameters.…”
Section: Resultsmentioning
confidence: 99%
“…The bands at 211, 335, 487, and 596 cm –1 are due to the symmetric and antisymmetric bending of oxygen atom in M–O bond at octahedral voids. Finally, the bands appeared around 450, 567, and 659 cm –1 as the shoulders of the intense 487 and 703 Raman bands appeared due to the differences in charge and ionic radii of Ni and Fe ions, producing larger Ni(II)–O bonds in comparison to Fe(III)–O bond, 21 and consequently changing the energy of their bending and stretching vibrations. However, although a same number of dispersion bands appeared in the Raman spectrum of the Co 0.5 Ni 0.5 Fe 2 O 4 sample (Figure 3, trace c), their positions remained in between the positions of corresponding modes in NiFe 2 O 4 and CoFe 2 O 4 samples.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although the magnetic properties of spinel cobalt and nickel ferrites have been studied by several research groups, 3,8,13,24,21,38,39 there exist very few reports in the literature on the magnetic properties of Co 0.5 Ni 0.5 Fe 2 O 4 NPs, especially beyond room temperature. 28,36 Furthermore, although Rosnan et al reported a coercivity field ( H c ) of 603.26 Oe for their Co 0.5 Ni 0.5 Fe 2 O 4 NPs fabricated by co-precipitation and postgrowth sintering at 900 °C for 10 h, 36 Raju et al reported a H c value of just 250 Oe for their Co 0.5 Ni 0.5 Fe 2 O 4 NPs fabricated by the citrate mediated sol–gel method.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum value of the ZFC curve at T B , shifts towards higher temperatures as the Co 2+ content increases, that is, T B = 25 K, 62 K, 114 K, 170 K, and 240 K for Co_0, Co_1, Co_2, Co_3 and Co_4, respectively. Since the phenomenon of SPM blocking is related to magnetic anisotropy, the increasing of blocking temperature can be attributed to an increased particle anisotropy [53].…”
Section: Resultsmentioning
confidence: 99%